Higher Incidence of Chronic Thromboembolic Pulmonary Hypertension After Acute Pulmonary Embolism in Asians Than in Europeans: A Meta-Analysis - Pang, Wenyi; Zhang, Zhu; Wang, Zenghui; Zhen, Kaiyuan; Zhang, Meng; Zhang, Yunxia; Gao, Qian; Zhang, Shuai; Tao, Xincao; Wan, Jun; Xie, Wanmu; Zhai, Zhenguo (Frontiers in Medicine, 2021)
Aim: To summarize the incidence of right heart catheter diagnosed chronic thromboembolic pulmonary hypertension (CTEPH) after acute pulmonary embolism (PE) in a meta-analysis. Methods: Cohort studies reporting the incidence of CTEPH after acute PE were identified via search of Medline, Embase, China National Knowledge Infrastructure and WanFang databases. Results: Twenty-two cohort studies with 5,834 acute PE patients were included. Pooled results showed that the overall incidence of CTEPH was 2.82% (95% CI: 2.11–3.53%). Subgroup analyses showed higher incidence of CTEPH in Asians than Europeans (5.08 vs. 1.96%, p = 0.01), in retrospective cohorts than prospective cohorts (4.75 vs. 2.47%, p = 0.02), and in studies with smaller sample size than those with larger sample size (4.57 vs. 1.71%, p < 0.001). Stratified analyses showed previous venous thromboembolic events and unprovoked PE were both significantly associated with increased risk of CTEPH (OR = 2.57 and 2.71, respectively; both p < 0.01). Conclusions: The incidence of CTEPH after acute PE is ~3% and the incidence is higher in Asians than Europeans. Efforts should be made for the early diagnosis and treatment of CTEPH in PE patients, particularly for high-risk population.